Population Growth of Fruit Flies (Drosophilla melanogaster) Using The Barangan Banana (Musa paradisiaca) was tested in the FKIP UISU Medan Laboratory - Fefiani, Yusri; Warsodirejo, Pandu Prabowo (International Journal for Educational and Vocational Studies, 2020)
This study aims to: 1) recognize fruit flies (Drosophila melanogaster), 2) morphologically distinguish adult fruit fly sex, 3) study the growth of fruit fly populations. The practicum was held on August 20, 2019 in the Biology Education Laboratory FKIP UISU. The working principle of practicum is making food as a medium for fruit fly culture (a mixture of bananas, cassava tape, benzoate), etherization and observation, observing the growth of fruit fly populations. Observations were made by counting the number of live flies and dead flies, the sex ratio of flies. Observations were carried out every day, for 15 days (20 August 2019 - 3 September 2019). The results of the analysis show that: 1) population growth of Drosophila melanogaster includes logistic growth models with S-shaped curves, 2) sex of adult fruit flies can be morphologically distinguished through body size, abdominal shape, genital comb and external genital organs in the abdomen. Based on the results and discussion, the following conclusions are obtained: 1) fruit flies including insects undergoing perfect metamorphosis (egg phase, larvae, pupa, imago), 2) differences in adult fruit fly sex can be seen from body size, abdomen shape, presence of genital comb, external genital organs in the abdomen, 3) population growth of fruit flies including logistic growth models in the form of S curves, influenced by environmental factors